Conservation of Resources, Burnout, and Other Selected Behavioral Variables among Law Enforcement Officers: A Quantitative Analysis - C. Niebusch, Richard; R. Moran, Nathan (Asian Crime and Society Review, 2019)
The purpose of this study is to determine the relationship between personal and social resources and burnout for police officers. Current conceptualizations of the condition of burnout are challenged as being too phenomenological and ambiguous, and consequently, not given to direct empirical testing. The conservation of resources model is based on the supposition that people strive to retain, protect, and build resources as a means to protect them from the impacts of burnout. The model proposes that the effects of stress (i.e. burnout) can be manifested in personal and professional attitudes and attributes, which can measure burnout using self-reports to provide strong support for the conservation of resources model, in that, personal and professional demands are related to the exhaustion component of burnout, whereas personal and professional resources can be compiled to counteract the negative impact of the burnout condition. Highly similar patterns of burnout resistance factors were witnessed in police officers in two department precincts. In addition, results confirmed the positive influence of key demographic variables in burnout resistance using the conservation of resources model. Participants in this study are all sheriff’s deputies with a populous county in a Pacific Northwestern state. Four instruments will be used in this quantitative study for data collection (a) a series of demographic questions, (b) the Organizational Citizenship Behavior, (c) the PANASX Scale, and (d) The Maslach Burnout Inventory.